Tunnicliff, Rigby, and Staton families papers
Correspondence, writings, notes, genealogical material, printed material, and newspaper clippings. Chiefly correspondence of John Cooper Tunnicliff, his wife Cornelia Hunter Tunnicliff, and their six children of Galesburg, Ill., and later of Moline, Ill. Also includes correspondence of Cornelia's mother, Sarah Ellen Hunter. Subjects include family affairs, the Methodist Church, temperance movement, hydropathy, trips to England in 1878 and 1909, and the 1904 Louisiana Purchase Exposition in St. Louis. Genealogical material pertains to the Cooper, Hunter, Rigby, Smith, and Tunnicliff families.
Library of Congress Prints and Photographs Division.
American families living chiefly in West Virginia, Illinois, and Iowa.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hunter, Sarah Ellen -- Correspondence; Tunnicliff, Cornelia Hunter -- Correspondence; Tunnicliff, John Cooper -- Correspondence; Cooper family; Hunter family; Rigby family; Smith family; Staton family; Tunnicliffe family; Methodist Church (U.S.); Hydrotherapy; Temperance; England -- Description and travel; Galesburg (Ill.) -- History; Illinois -- Social life and customs; Moline (Ill.) -- History